Technological prospecting on patent bases focusing on food dyes and pigments obtained from natural sources (Research, Society and Development, 2021)
The food industry has been challenged to find natural and healthy alternatives in the development of new products, without changing its safety and main characteristics. In this context, natural dyes appear as an alternative to the substitution of synthetic dyes in the food segment. Patent protection is shown to be a protection tool for inventors as a result of various research and innovations. This paper aimed to explore patent technologies regarding food dyes and pigments obtained from natural and renewable sources, in order to identify technological advances and market trends in the national and international scenario. A technological mapping was carried out based on patent bases, using the search and analysis software, ORBIT from Questel and the Brazilian INPI database. It was possible to evidence a growth in deposits, highlighting the incentives for research, development and innovation. China was the main country that filed for patents. It was observed that both nationally and internationally, the main interested parties in protecting their technologies were private companies, being CHR. HANSEN the company with the highest number of patents in its portfolio. The field of technology relates mainly to the areas of the food industry, materials chemistry and the pharmaceutical industry.